2015
DOI: 10.1039/c5nr02402a
|View full text |Cite
|
Sign up to set email alerts
|

Mn(ii) mediated degradation of artemisinin based on Fe3O4@MnSiO3-FA nanospheres for cancer therapy in vivo

Abstract: Artemisinin (ART) is a natural drug with potent anticancer activities related with Fe(2+) mediated cleavage of the endoperoxide bridge in ART. Herein, we reported that Mn(2+) could substitute for Fe(2+) to react with ART and generate toxic products, inducing a much higher anticancer efficiency. On this basis, we prepared pH-responsive Fe3O4@MnSiO3-FA nanospheres which can efficiently deliver hydrophobic ART into tumors in mice models. Mn(2+) was released in acidic tumor environments and intracellular lysosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…In principle, drug encapsulation can improve specificity and bioavailability as well as alter pharmacokinetic properties of the drug. 135 The recent years have seen a remarkable surge of studies exploring various approaches in nanomedicine, ranging from liposomal delivery, [136][137][138][139][140][141] encapsulation with other drugs or biomolecules including transferrin, [142][143][144][145] encapsulation with specific properties such as magnetic or pH-responsive liposomes, [143][144][145][146] novel metal based nanostructures, 146,147 solid lipid nanoparticles (SLNs), and niosomes. 148 In general, these studies have consistently reported positive results with significant enhancements to efficacy and improved selectivity.…”
Section: Enhancement Of Anticancer Activitymentioning
confidence: 99%
“…In principle, drug encapsulation can improve specificity and bioavailability as well as alter pharmacokinetic properties of the drug. 135 The recent years have seen a remarkable surge of studies exploring various approaches in nanomedicine, ranging from liposomal delivery, [136][137][138][139][140][141] encapsulation with other drugs or biomolecules including transferrin, [142][143][144][145] encapsulation with specific properties such as magnetic or pH-responsive liposomes, [143][144][145][146] novel metal based nanostructures, 146,147 solid lipid nanoparticles (SLNs), and niosomes. 148 In general, these studies have consistently reported positive results with significant enhancements to efficacy and improved selectivity.…”
Section: Enhancement Of Anticancer Activitymentioning
confidence: 99%
“…Chen and coworkers prepared pH-responsive Fe 3 O 4 @MnSiO 3 -FA NPs aiming the efficiently deliver of ART and Mn 2ĂŸ into tumours in mice models. Manganese ions released in acidic environments and intracellular lysosomes could interact with ART to kill cancer cells [54]. The magnetic titanium nanocomposites coated with hyaluronic acid (HA-TiO 2 -IONPs) containing ART exhibited high cytotoxicity in MCF-7 lines and combined with laser irradiation provided best anti-tumour efficacy [55].…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…So far, a variety of imaging technologies have been developed and used in clinical medicine, including MRI, 62 FOI, 63 X-ray computed tomography (CT) imaging, 64 positron-emission tomography (PET) imaging, 65 and ultrasound imaging. 67,68 For example, preclinical photoacoustic (PA) imaging is a hybrid modality, combining the highcontrast and spectroscopic-based specificity of optical imaging with the high spatial resolution of ultrasound imaging. MRI has exceptional spatial resolution but lacks sensitivity.…”
Section: Multi-modal Imagingmentioning
confidence: 99%